A panoramic view of the circumgalactic medium in the photoionized precipitation model. Issue 3 (4th September 2021) - Roy, Manami; Nath, Biman B; Voit, G M
ABSTRACT: We consider a model of the circumgalactic medium (CGM) in which feedback maintains a constant ratio of cooling time to free-fall time throughout the halo, so that the entire CGM is marginally unstable to multiphase condensation. This 'precipitation model' is motivated by observations of multiphase gas in the cores of galaxy clusters and the haloes of massive ellipticals. From the model, we derive the density and temperature profiles for the CGM around galaxies with masses similar to the Milky Way. After taking into consideration the geometrical position of our Solar system in the Milky Way, we show that the CGM model is consistent with observed O vi, O vii, O viii column densities and the ratio of O vii and O viii column densities only if temperature fluctuations with a lognormal dispersion σln  T ∼ 0.6–1.0 are included. We show that O vi column densities observed around star-forming galaxies require systematically greater values of σln  T than around passive galaxies, implying a connection between star formation in the disc and the state of the CGM. Photoionization by an extragalactic ultraviolet background radiation does not significantly change these CGM features for galaxies like the Milky Way but has much greater and significant effects on the CGM of lower mass galaxies.